2007
DOI: 10.1017/s1368980007441477
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and knowledge about osteoporosis risk prevention: a survey of New Zealand women

Abstract: Objectives: The purpose of this study was to investigate the knowledge and health beliefs regarding osteoporosis risk factors of New Zealand women aged 20-49 years. Design: A descriptive, web-based survey. Subjects: An opportunistic sample of 622 women aged between 20 and 49 years living in Auckland, New Zealand was recruited by email. Results: There was a moderate level of knowledge about osteoporosis risk factors among the women surveyed, with a mean total score for all subjects of 16.4 (standard deviation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
67
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 22 publications
(33 reference statements)
24
67
1
4
Order By: Relevance
“…As in previous studies, knowledge scores in our cohort were directly correlated with education levels [27,41], however even among participants with higher education levels in our cohort, mean knowledge scores were still lower than that reported among most studies from the U.S., Canada and New Zealand that were conducted primarily among Caucasian cohorts [14,1619,42]. It is not clear whether this lack of knowledge is related to low prioritization of osteoporosis among other health conditions in China, or inaccurate or ineffective dissemination of information regarding osteoporosis-related risk factors and preventive measures.…”
Section: Discussionsupporting
confidence: 60%
“…As in previous studies, knowledge scores in our cohort were directly correlated with education levels [27,41], however even among participants with higher education levels in our cohort, mean knowledge scores were still lower than that reported among most studies from the U.S., Canada and New Zealand that were conducted primarily among Caucasian cohorts [14,1619,42]. It is not clear whether this lack of knowledge is related to low prioritization of osteoporosis among other health conditions in China, or inaccurate or ineffective dissemination of information regarding osteoporosis-related risk factors and preventive measures.…”
Section: Discussionsupporting
confidence: 60%
“…Studies have shown that either people believe osteoporosis is an inevitable part of aging and do not take it as a serious disease that may even cause death [11,21] or consider other diseases, i.e., heart diseases, HIV and diabetes more serious than osteoporosis [21]. Although knowledge is a key component in promoting self-care, knowledge alone still cannot result in the practice of preventive behavior or positive attitude [18].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, both Ziccardi et al and Von Hurst and Wham found that at least 79% of women in their studies recognized family history as a risk factor. 21,22 Although many participants knew the importance of sun exposure, a calcium-rich diet, and exercise to prevent osteoporosis, only few knew the benefit of sardines, tuna, and broccoli as good sources of calcium for lactoseintolerant individuals.…”
Section: Knowledge About Osteoporosismentioning
confidence: 99%
“…21,22 Therefore, increasing the level of knowledge about non-dairy sources of calcium may increase dietary calcium intake among women, particularly those who are lactose intolerant or simply dislike the taste of dairy products.…”
Section: Knowledge About Osteoporosismentioning
confidence: 99%